2021
DOI: 10.46474/jds.938258
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Assessment of an Extended Learning Environment in Interior Design Studio

Abstract: This paper presents a critical assessment of an interior design studio that was constructed face-to-face then online as an extended studio environment through spatial and technological means. In the Interior Design Studio III, students were expected to design an experiential retail store aiming at answering the contemporary customer and brand interactive experience. The concept of ‘interactive experience’ was central not only in terms of a project outcome but also of the studio process: an experiential learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The interaction of the body with the built environment should be taken into account in a holistic manner, where experience is embodied on a multidimensional level, in order to produce a spatial experience that is both functionally and aesthetically integrated. (Ceylanli & Yanas, 2021) Gamification in learning is one of the perspectives in integrated metaverse that has been explored in education such as in architecture and city planning. Due to the nature of the building environment itself, it has been reported that the construction business has the third highest record of workplace accidents, (Mohd et al, 2019).…”
Section: Figure 10 Digital Fabrication With Computer Aided Design (Ca...mentioning
confidence: 99%
“…The interaction of the body with the built environment should be taken into account in a holistic manner, where experience is embodied on a multidimensional level, in order to produce a spatial experience that is both functionally and aesthetically integrated. (Ceylanli & Yanas, 2021) Gamification in learning is one of the perspectives in integrated metaverse that has been explored in education such as in architecture and city planning. Due to the nature of the building environment itself, it has been reported that the construction business has the third highest record of workplace accidents, (Mohd et al, 2019).…”
Section: Figure 10 Digital Fabrication With Computer Aided Design (Ca...mentioning
confidence: 99%